The oral microbiome is associated with HPA axis response to a psychosocial stressor - Eleftheria G. Charalambous; Sophie B. Mériaux; Pauline Guebels; Claude P. Muller; Fleur A. D. Leenen; Martha M. C. Elwenspoek; Ines Thiele; Johannes Hertel; Jonathan D. Turner (Scientific Reports, 2024)
Abstract Intense psychosocial stress during early life has a detrimental effect on health-disease balance in later life. Simultaneously, despite its sensitivity to stress, the developing microbiome contributes to long-term health. Following stress exposure, HPA-axis activation regulates the “fight or flight” response with the release of glucose and cortisol. Here, we investigated the interaction between the oral microbiome and the stress response. We used a cohort of 115 adults, mean age 24, who either experienced institutionalisation and adoption (n = 40) or were non-adopted controls (n = 75). Glucose and cortisol measurements were taken from participants following an extended socially evaluated cold pressor test (seCPT) at multiple time points. The cohort´s oral microbiome was profiled via 16S-V4 sequencing on microbial DNA from saliva and buccal samples. Using mixed-effect linear regressions, we identified 12 genera that exhibited an interaction with host’s cortisol-glucose response to stress, strongly influencing intensity and clearance of cortisol and glucose following stress exposure. Particularly, the identified taxa influenced the glucose and cortisol release profiles and kinetics following seCPT exposure. In conclusion, our study provided evidence for the oral microbiome modifying the effect of stress on the HPA-axis and human metabolism, as shown in glucose-cortisol time series data.